2018
DOI: 10.15561/20755279.2019.0102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preparation period exercises on the hematological parameters of the taekwondo athletes

Abstract: Purpose: This study aimed at examining the effects of preparation period exercises, which were applied for eight weeks to elite level taekwondo athletes, on the hematological parameters. Material: Totally 21 athletes with international degrees from the university taekwondo team participated in this study, 12 of whom were female (Mean age: 20.3 - Mean exercise age: 8.8) and 9 of whom were male athletes (Mean age: 20.3 - Mean exercise age: 9.5). The participants attended an 8-week exercise program for 5 days a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This study revealed that the increases in the hemoglobin, hematocrit, MCH, and RBC, that carry oxygen to the tissues, values and are related to plasma losses after exercise, were observed to be largely coherent with the discipline [19,21,25]. On the other hand, in a study conducted in 2020 in which the effects of a short-term training program applied under hypoxic conditions on the hematological parameters of Korean disabled cycling national team athletes was investigated, it was revealed that there were no significant differences in oxygen-transporting capacity parameters.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This study revealed that the increases in the hemoglobin, hematocrit, MCH, and RBC, that carry oxygen to the tissues, values and are related to plasma losses after exercise, were observed to be largely coherent with the discipline [19,21,25]. On the other hand, in a study conducted in 2020 in which the effects of a short-term training program applied under hypoxic conditions on the hematological parameters of Korean disabled cycling national team athletes was investigated, it was revealed that there were no significant differences in oxygen-transporting capacity parameters.…”
Section: Discussionmentioning
confidence: 86%
“…It was observed in the study that there was neutrophil (granulocyte) increase immediately after exercise in male and female athletes as the amount of WBC increased. Similarly, several studies involving both sedentary individuals and nondisabled athletes reported that the amount of WBC, including neutrophil increase during the early period of exercise [20,21,25]. On the other hand, in a study investigating the pre-and post-competition hematological parameters of a male Brazilian Jiu-Jitsu Paradesport athlete, who was an elite paralympic athlete, it was shown that WBC and monocytes increased significantly in the early period after the competition, while lymphocytes decreased.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Yeh et al [29] stated that there was no statistically significant change in female and Note: PLT: platelet male athletes' WBC level before and after the 12-week exercise period. Ergün et al [30] have found that aerobic exercises which are applied regularly three days a week do not affect WBC level in middle-aged men.In the study of Boylı et al [31] declared that there was no significant increase in taekwondo athletes' WBC parameters in the preparation period training. These results in the literature are consistent with our research results.…”
Section: Discussionmentioning
confidence: 96%